The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/09581596.2016.1240356
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge needs and the ‘savvy’ child: teenager perspectives on banning food marketing to children

Abstract: Food marketing to children is a powerful factor in the health of young people. In Canada, one proposed measure to protect young people is to ban all food and beverage marketing to children under age 13. Since policy initiatives should consider the voices of those directly impacted, we conducted focus groups with teenagers aged 12-14 -precisely those individuals who would be directly impacted by, or just over, the age threshold proposed. The majority of teenagers consulted were opposed to a ban on food marketin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
4
14
0
1
Order By: Relevance
“…Adolescents in our study commented on the imbalance between unhealthy and healthy food marketing and advertising and shared their concerns on this issue. These were comparable to qualitative work by Elliot (2017) among regular-weight adolescents who affirmed that advertisers deliberately try to mislead consumers [43]. This study, however, differs from ours in that adolescents expressed concern for younger children, and not themselves, as being a target of these manipulations [43].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Adolescents in our study commented on the imbalance between unhealthy and healthy food marketing and advertising and shared their concerns on this issue. These were comparable to qualitative work by Elliot (2017) among regular-weight adolescents who affirmed that advertisers deliberately try to mislead consumers [43]. This study, however, differs from ours in that adolescents expressed concern for younger children, and not themselves, as being a target of these manipulations [43].…”
Section: Discussionsupporting
confidence: 84%
“…These were comparable to qualitative work by Elliot (2017) among regular-weight adolescents who affirmed that advertisers deliberately try to mislead consumers [43]. This study, however, differs from ours in that adolescents expressed concern for younger children, and not themselves, as being a target of these manipulations [43]. Although much of the research is descriptive in nature, studies have suggested a positive link between advertisements for unhealthy food on the Internet and in advergames and children’s desire for and consumption of the foods promoted [44, 45].…”
Section: Discussionsupporting
confidence: 76%
“…The reported results are of great concern because it is well established that different child-oriented marketing techniques, such as the use of cartoon characters and similar elements on food packaging, significantly influence children’s food choices and preferences [21,23,48]. By using such child-oriented marketing techniques, children are encouraged to like and want products which they see as “fun” and “good tasting” [49]. When foods are accompanied with children-familiar characters, children are convinced it tastes and looks better and would more likely ask their parents to buy it for them [50].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these two age groups should be studied separately [10]. Nevertheless, Elliot [30] highlights that many of the FE studies that include teenagers include children under 13 [10,29,31,32]. Despite the strong interest and emerging research concerning the effects of food marketing on child health, there is limited environmental and public health research that focuses on its potential impacts on teenage food purchasing perceptions and dietary behaviours [10,29,30,31,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…While coding schemes to classify various child-directed advertising criteria have been developed [36,45,50,51], most studies simply coded for the presence or absence of each criterion [19,31,36,50,51]. Further, such coding schemes applied predetermined criteria instead of consulting target populations to determine what factors are important to them; this tailoring of criteria is important to fully understand how advertising influences specific populations of interest [23,30]. To date, researchers have not yet considered the relative influence of each criterion on teens’ perceived purchasing behaviours.…”
Section: Introductionmentioning
confidence: 99%